Analisis Gramatika Kata Kenosis Di Dalam Filipi 2:7 - Samuel Lengkong (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2021)
Theological debate about the word “kenosis, the question is what Christ emptied of Himself. Discussions about the Doctrine of Christ or Christology are indeed endlessly discussed and debated, both by heretics and by Christian apologists. In this study, two approaches are used, namely the study of literature and the study of the theological meaning of the phrase